Bullying Behavior of High School Students in the School Environment - Aprilia, Devi (Lembaga Bale Literasi, 2023)
Bullying behavior in the school environment can create an environment that is less supportive of student development, both in the academic and social fields. Bullying behavior can hurt students, leaving them feeling unwanted and rejected by their environment. This will certainly have an effect on various student activities at school. Researchers took the title